(untitled) (Modern education and development, 2025)
The article discusses the basics and practical applications of disease detection based on neural networks. The article provides detailed information about the main types of neural networks, in particular, feedforward networks, convolutional networks (CNN), recurrent networks (RNN) and deep neural networks (DNN). It also analyzes the application of these networks in such fields as oncology, cardiology, neurology, endocrinology and infectious diseases, their effectiveness and advantages in disease detection. The article also reviews the widespread use of neural networks in medicine, along with limitations, data security and understandability issues.